A hydrolytic tin-free antifouling paint for ship bottom and a method for preparing the same

CN122381636BActive Publication Date: 2026-09-11福建海轮新材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610856756.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-15
Publication Date
2026-09-11
Estimated Expiration
2046-06-15

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种水解型无锡船底防污漆及其制备方法,解决了上述背景技术中提出的活性成分过早流失,可能会造成防污期效缩短,无法保证长效防污效果的问题

Benefits of technology

[0024] 1. In this invention, during the treatment of antifouling active components, supercritical CO2 fluid is used to encapsulate and granulate dihydrocapsaicin, 4,5-dichloro-2-n-octyl-3-isothiazolinone, and a porous silica carrier, and the particle size and wall thickness of the microcapsules are controlled to ensure a stable loading of the antifouling active components, while avoiding premature loss of active ingredients, thereby achieving long-term release of the antifouling function and reducing the need for recoating the antifouling paint.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention relates to the field of marine coating technology and discloses a hydrolytic antifouling paint for Wuxi ship bottoms and its preparation method. The method includes the preparation of a modified acrylate resin prepolymer, microencapsulation of antifouling active components, synthesis of a hydrolytic self-polishing base material, formulation of the finished antifouling paint, and curing treatment of the antifouling paint. By using supercritical CO2 fluid to encapsulate and granulate dihydrocapsaicin, 4,5-dichloro-2-n-octyl-3-isothiazolinone, and a porous silica carrier, and by controlling the particle size and wall thickness of the microcapsules, a stable loading of the antifouling active components is ensured, achieving long-term release of the antifouling function and reducing the recoating requirement of the antifouling paint. By adding styrene-acrylate copolymer, zinc acrylate resin, and organobentonite to a mixed solvent of xylene and propylene glycol methyl ether acetate and stirring to dissolve, and by controlling the mass ratio of styrene to acrylate and the acid value of zinc acrylate resin, the hydrolytic stability of the base material is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of marine coating technology, specifically to a hydrolytic antifouling paint for ship bottoms made in Wuxi and its preparation method. Background Technology

[0002] Antifouling paint is a coating applied to the bottom of ships and underwater facilities. It is usually applied over anti-rust paint and is the outermost layer. It is used to prevent increased navigation resistance and corrosion of facilities caused by the attachment of marine organisms. It achieves its antifouling function through the leaching or hydrolysis of toxic substances in the paint film and has the characteristics of stable release of toxicity and resistance to seawater impact. This coating is divided into traditional type, self-polishing type, low surface energy type and other categories.

[0003] Currently, due to the multiple processes involved in the preparation of marine antifouling paint, the antifouling active components are not microencapsulated during the preparation of the antifouling paint. Instead, they are only mixed physically, which cannot guarantee a stable load of the antifouling active components. If the active ingredients are lost too early, it may shorten the antifouling period and fail to guarantee a long-lasting antifouling effect.

[0004] Therefore, a hydrolytic antifouling paint for ship bottoms made of tin and its preparation method are proposed to solve the above problems. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a hydrolytic antifouling paint for Wuxi ship bottoms and its preparation method, which solves the problem mentioned in the background art that the premature loss of active ingredients may lead to a shortened antifouling period and an inability to guarantee long-lasting antifouling effects.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a hydrolytically based antifouling paint for ship bottoms, comprising the following steps:

[0007] Step 1: Preparation of modified acrylate resin prepolymer: Methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and chain transfer agent are mixed in a mass ratio of 35-45:20-30:8-12:0.5-1.5, protected by nitrogen gas, heated to 75℃-85℃, and prepolymerized by stirring at 800-1200 r / min for 1.5-2.5 h to obtain a prepolymer with a solid content of 40%-50%.

[0008] Step 2: Microencapsulation of antifouling active components. Dihydrocapsaicin, 4,5-dichloro-2-n-octyl-3-isothiazolinone, and porous silica carrier are mixed at a mass ratio of 1-2:0.5-1:5-8. The mixture is then coated and granulated using supercritical CO2 fluid at a pressure of 15-25 MPa and a temperature of 40-50℃ to obtain microcapsules with a particle size of 10-30 μm.

[0009] Step 3: Synthesis of self-polishing base material by hydrolysis. Styrene-acrylate copolymer, zinc acrylate resin and organobentonite are added to a mixed solvent of xylene and propylene glycol methyl ether acetate in a mass ratio of 25-35:10-20:1-3. The volume ratio of xylene to propylene glycol methyl ether acetate in the mixed solvent is 2-4:1. The mixture is heated to 60℃-70℃ and stirred at 600-1000 r / min for 2-3 hours to dissolve the material.

[0010] Step 4: Preparation of the antifouling paint finished product. By mass, take 20-30 parts of the prepolymer obtained in Step 1, 5-15 parts of the microcapsules obtained in Step 2, 15-25 parts of the base material obtained in Step 3, 5-10 parts of cuprous oxide, 8-12 parts of zinc oxide, 10-15 parts of talc, 1-3 parts of organobentonite, and 10-15 parts of xylene. First, mix the prepolymer and the base material and disperse them at 1500-2000 r / min for 20-30 min. Then add the remaining components and grind until the fineness is ≤30μm to obtain the antifouling paint for the ship bottom.

[0011] Preferably, in step one, the chain transfer agent is mercaptoethanol or dodecyl mercaptan, the heating rate during prepolymerization is 3-5℃ / min, and the linear velocity of the stirring blade tip is 8-12m / s.

[0012] Preferably, in step one, the hydroxyl value of hydroxyethyl methacrylate is 100-130 mgKOH / g. After the prepolymer synthesis is completed, 0.1-0.3% of hydroquinone polymerization inhibitor by mass of the prepolymer is added, and after stirring evenly, the temperature is lowered to below 40°C before discharge.

[0013] Preferably, in step two, the flow rate of the supercritical CO2 fluid is 5-10 L / min, the system pressure fluctuation range is kept ≤ ±0.5 MPa and the temperature fluctuation range is kept ≤ ±1℃ during the granulation process, and the wall thickness of the microcapsules is controlled at 2-5 μm.

[0014] Preferably, in step two, the porous silica carrier has a specific surface area of ​​300-500 m² / g and a pore size of 5-10 nm. Before microencapsulation, the porous silica carrier is dried in an oven at 120°C for 2-3 hours and then cooled to room temperature before being mixed with the antifouling active ingredient.

[0015] Preferably, in step three, the mass ratio of styrene to acrylate in the styrene-acrylate copolymer is 1-2:1, the acid value of the zinc acrylate resin is 50-80 mg KOH / g, and the cation exchange capacity of the organobentonite is ≥100 mmol / 100g.

[0016] Preferably, in step four, the purity of cuprous oxide is ≥99%, and the particle size distribution D50 is 2-5 μm;

[0017] The purity of zinc oxide is ≥99.5%, and the particle size distribution D50 is 1-3μm; the whiteness of talc is ≥90%, and the loss on ignition is ≤5%.

[0018] Preferably, in step four, the grinding is carried out using a three-roll mill, with the front roller speed being 100-150 r / min, the middle roller speed being 200-250 r / min, the rear roller speed being 300-350 r / min, and the roller gap being 0.05-0.1 mm.

[0019] Preferably, the method further includes step five: antifouling paint curing treatment, in which the antifouling paint obtained in step four is placed in a sealed desiccator and allowed to cure for 48-72 hours at a temperature of 25±2℃ and a relative humidity of 50±5%. During the curing period, the paint is stirred once every 12 hours at a stirring speed of 300-500 r / min for 5-10 minutes each time.

[0020] A hydrolytic antifouling paint for ship bottoms made in Wuxi, the antifouling paint being composed of the following raw materials in parts by weight:

[0021] 20-30 parts of modified acrylate resin prepolymer, 5-15 parts of antifouling active component microcapsules, 15-25 parts of hydrolyzed self-polishing base material, 5-10 parts of cuprous oxide, 8-12 parts of zinc oxide, 10-15 parts of talc, 1-3 parts of organobentonite, and 10-15 parts of xylene.

[0022] The structure of the hydrolytic antifouling paint for Wuxi ship bottoms includes a surface hydrolytic release layer and an inner antifouling functional skeleton. The surface hydrolytic release layer is composed of a hydrolytic self-polishing base material, and the inner antifouling functional skeleton is formed by mixing and curing antifouling active component microcapsules, cuprous oxide, zinc oxide and talc.

[0023] Compared with the prior art, the present invention provides a hydrolytic antifouling paint for tin-based ship bottoms and its preparation method, which has the following beneficial effects:

[0024] 1. In this invention, during the treatment of antifouling active components, supercritical CO2 fluid is used to encapsulate and granulate dihydrocapsaicin, 4,5-dichloro-2-n-octyl-3-isothiazolinone, and a porous silica carrier, and the particle size and wall thickness of the microcapsules are controlled to ensure a stable loading of the antifouling active components, while avoiding premature loss of active ingredients, thereby achieving long-term release of the antifouling function and reducing the need for recoating the antifouling paint.

[0025] 2. In this invention, during the preparation of the hydrolytic self-polishing base material, the styrene-acrylate copolymer, zinc acrylate resin, and organic bentonite are added to a mixed solvent of xylene and propylene glycol methyl ether acetate and stirred to dissolve. The mass ratio of styrene to acrylate and the acid value of zinc acrylate resin are controlled to ensure the hydrolytic stability of the base material. At the same time, controllable polishing of the paint film surface is achieved, maintaining the self-polishing performance of the antifouling paint and improving the smoothness of the paint film.

[0026] 3. In this invention, during the preparation of the antifouling paint, the modified acrylic resin prepolymer, antifouling active component microcapsules, hydrolyzed self-polishing base material and various fillers are mixed, dispersed and ground in sequence, and the finished product is cured to ensure the density and uniformity of the paint film, while improving the adhesion between the paint film and the substrate, enhancing the construction adaptability of the antifouling paint, and extending the service life of the antifouling paint. Detailed Implementation

[0027] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0028] Example 1: A method for preparing a hydrolytically based tin-free antifouling paint for ship bottoms, comprising the following steps:

[0029] Step 1: Preparation of modified acrylate resin prepolymer: Methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and chain transfer agent are mixed in a mass ratio of 35:20:8:0.5, nitrogen gas is introduced for protection, the temperature is raised to 75℃, and the mixture is stirred at 800 r / min for 1.5 h to obtain a prepolymer with a solid content of 40%.

[0030] Step 2: Microencapsulation of antifouling active components. Dihydrocapsaicin, 4,5-dichloro-2-n-octyl-3-isothiazolinone and porous silica carrier are mixed at a mass ratio of 1:0.5:5 and encapsulated and granulated using supercritical CO2 fluid at a pressure of 15 MPa and a temperature of 40 °C to obtain microcapsules with a particle size of 10 μm.

[0031] Step 3: Synthesis of self-polishing base material by hydrolysis. Styrene-acrylate copolymer, zinc acrylate resin and organobentonite are added to a mixed solvent of xylene and propylene glycol methyl ether acetate in a mass ratio of 25:10:1. The volume ratio of xylene to propylene glycol methyl ether acetate in the mixed solvent is 2:1. The mixture is heated to 60°C and stirred at 600 r / min for 2 h to dissolve, thus obtaining the base material.

[0032] Step 4: Preparation of the antifouling paint finished product. By mass, take 20 parts of the prepolymer obtained in Step 1, 5 parts of the microcapsules obtained in Step 2, 15 parts of the base material obtained in Step 3, 5 parts of cuprous oxide, 8 parts of zinc oxide, 10 parts of talc, 1 part of organobentonite, and 10 parts of xylene. First, mix the prepolymer and the base material and disperse them at 1500 r / min for 20 min. Then add the remaining components and grind them until the fineness is ≤30μm to obtain the antifouling paint for the bottom of the ship.

[0033] In step one, mercaptoethanol is used as the chain transfer agent, the heating rate during prepolymerization is 3℃ / min, and the linear velocity of the stirring blade tip is 8m / s.

[0034] In step one, the hydroxyl value of hydroxyethyl methacrylate is 100 mg KOH / g. After the prepolymer synthesis is completed, 0.1% of hydroquinone polymerization inhibitor by mass of the prepolymer is added, stirred evenly, and then cooled to below 40°C before discharge.

[0035] In step two, the flow rate of supercritical CO2 fluid is 5 L / min, and the system pressure fluctuation range is kept ≤ ±0.5 MPa and the temperature fluctuation range is kept ≤ ±1℃ during granulation. The wall thickness of the microcapsules is controlled at 2 μm.

[0036] In step two, the porous silica carrier has a specific surface area of ​​300 m² / g and a pore size of 5 nm. Before microencapsulation, the porous silica carrier is dried in an oven at 120°C for 2 hours and then cooled to room temperature before being mixed with the antifouling active ingredient.

[0037] In step three, the mass ratio of styrene to acrylate in the styrene-acrylate copolymer is 1:1, the acid value of zinc acrylate resin is 50 mg KOH / g, and the cation exchange capacity of organobentonite is ≥100 mmol / 100g.

[0038] In step four, the purity of cuprous oxide is ≥99%, and the particle size distribution D50 is 2μm;

[0039] The purity of zinc oxide is ≥99.5%, and the particle size distribution D50 is 1μm; the whiteness of talc is ≥90%, and the loss on ignition is ≤5%.

[0040] In step four, a three-roll mill is used for grinding, with the front roller rotating at 100 r / min, the middle roller at 200 r / min, and the rear roller at 300 r / min, and the roller gap at 0.05 mm.

[0041] The method also includes step five: antifouling paint curing treatment. The antifouling paint obtained in step four is placed in a sealed desiccator and cured for 48 hours at a temperature of 23°C and a relative humidity of 45%. During the curing period, it is stirred once every 12 hours at a stirring speed of 300 r / min for 5 minutes each time.

[0042] A hydrolytic antifouling paint for ship bottoms made in Wuxi, comprising the following raw materials in parts by weight:

[0043] 20 parts modified acrylate resin prepolymer, 5 parts antifouling active component microcapsules, 15 parts hydrolyzed self-polishing base material, 5 parts cuprous oxide, 8 parts zinc oxide, 10 parts talc, 1 part organic bentonite, and 10 parts xylene.

[0044] The structure of the hydrolytic antifouling paint for Wuxi ship bottoms includes a surface hydrolytic release layer and an inner antifouling functional skeleton. The surface hydrolytic release layer is composed of a hydrolytic self-polishing base material, and the inner antifouling functional skeleton is formed by mixing and curing antifouling active component microcapsules, cuprous oxide, zinc oxide and talc.

[0045] Example 2: A method for preparing a hydrolytically based tin-free antifouling paint for ship bottoms, comprising the following steps:

[0046] Step 1: Preparation of modified acrylate resin prepolymer: Methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and chain transfer agent are mixed in a mass ratio of 40:25:10:1.0, nitrogen gas is introduced for protection, the temperature is raised to 80℃, and the mixture is stirred at 1000 r / min for 2.0 h to obtain a prepolymer with a solid content of 45%.

[0047] Step 2: Microencapsulation of antifouling active components. Dihydrocapsaicin, 4,5-dichloro-2-n-octyl-3-isothiazolinone and porous silica carrier were mixed at a mass ratio of 1.5:0.75:6.5 and encapsulated and granulated using supercritical CO2 fluid at a pressure of 20 MPa and a temperature of 45 °C to obtain microcapsules with a particle size of 20 μm.

[0048] Step 3: Synthesis of self-polishing base material by hydrolysis. Styrene-acrylate copolymer, zinc acrylate resin and organobentonite are added to a mixed solvent of xylene and propylene glycol methyl ether acetate in a mass ratio of 30:15:2. The volume ratio of xylene to propylene glycol methyl ether acetate in the mixed solvent is 3:1. The mixture is heated to 65°C and stirred at 800 r / min for 2.5 h to dissolve, thus obtaining the base material.

[0049] Step 4: Preparation of the antifouling paint finished product. By mass, take 25 parts of the prepolymer obtained in Step 1, 10 parts of the microcapsules obtained in Step 2, 20 parts of the base material obtained in Step 3, 7 parts of cuprous oxide, 10 parts of zinc oxide, 12 parts of talc, 2 parts of organobentonite, and 12 parts of xylene. First, mix the prepolymer and the base material and disperse them at 1750 r / min for 25 min. Then add the remaining components and grind them until the fineness is ≤30μm to obtain the antifouling paint for the ship bottom.

[0050] In step one, mercaptoethanol is used as the chain transfer agent, the heating rate during prepolymerization is 4℃ / min, and the linear velocity of the stirring blade tip is 10m / s.

[0051] In step one, the hydroxyl value of hydroxyethyl methacrylate is 115 mg KOH / g. After the prepolymer synthesis is completed, 0.2% of hydroquinone polymerization inhibitor by mass of the prepolymer is added, stirred evenly, and then cooled to below 40°C before discharge.

[0052] In step two, the flow rate of supercritical CO2 fluid is 7 L / min, the pressure fluctuation range of the system is kept ≤ ±0.5 MPa and the temperature fluctuation range is kept ≤ ±1℃ during the granulation process, and the wall thickness of the microcapsules is controlled at 3 μm.

[0053] In step two, the porous silica carrier has a specific surface area of ​​400 m² / g and a pore size of 7 nm. Before microencapsulation, the porous silica carrier is dried in an oven at 120°C for 2.5 h and then cooled to room temperature before being mixed with the antifouling active ingredient.

[0054] In step three, the mass ratio of styrene to acrylate in the styrene-acrylate copolymer is 1.5:1, the acid value of zinc acrylate resin is 65 mg KOH / g, and the cation exchange capacity of organobentonite is ≥100 mmol / 100g.

[0055] In step four, the purity of cuprous oxide is ≥99%, and the particle size distribution D50 is 3μm;

[0056] The purity of zinc oxide is ≥99.5%, and the particle size distribution D50 is 2μm; the whiteness of talc is ≥90%, and the loss on ignition is ≤5%.

[0057] In step four, a three-roll mill is used for grinding, with the front roller rotating at 125 r / min, the middle roller at 225 r / min, and the rear roller at 325 r / min, and the roller gap at 0.07 mm.

[0058] The method also includes step five: antifouling paint curing treatment. The antifouling paint obtained in step four is placed in a sealed desiccator and allowed to stand and cure for 60 hours at a temperature of 25°C and a relative humidity of 50%. During the curing period, the paint is stirred once every 12 hours at a stirring speed of 400 r / min for 7 minutes each time.

[0059] A hydrolytic antifouling paint for ship bottoms made in Wuxi, comprising the following raw materials in parts by weight:

[0060] 25 parts modified acrylate resin prepolymer, 10 parts antifouling active component microcapsules, 20 parts hydrolyzed self-polishing base material, 7 parts cuprous oxide, 10 parts zinc oxide, 12 parts talc, 2 parts organic bentonite, and 12 parts xylene.

[0061] The structure of the hydrolytic antifouling paint for Wuxi ship bottoms includes a surface hydrolytic release layer and an inner antifouling functional skeleton. The surface hydrolytic release layer is composed of a hydrolytic self-polishing base material, and the inner antifouling functional skeleton is formed by mixing and curing antifouling active component microcapsules, cuprous oxide, zinc oxide and talc.

[0062] Example 3: A method for preparing a hydrolytically based tin-free antifouling paint for ship bottoms, comprising the following steps:

[0063] Step 1: Preparation of modified acrylate resin prepolymer: Methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and chain transfer agent are mixed in a mass ratio of 45:30:12:1.5, nitrogen gas is introduced for protection, the temperature is raised to 85℃, and the mixture is stirred at 1200 r / min for 2.5 h to obtain a prepolymer with a solid content of 50%.

[0064] Step 2: Microencapsulation of antifouling active components. Dihydrocapsaicin, 4,5-dichloro-2-n-octyl-3-isothiazolinone and porous silica carrier are mixed at a mass ratio of 2:1:8. The mixture is then coated and granulated using supercritical CO2 fluid at a pressure of 25 MPa and a temperature of 50 °C to obtain microcapsules with a particle size of 30 μm.

[0065] Step 3: Synthesis of self-polishing base material by hydrolysis. Styrene-acrylate copolymer, zinc acrylate resin and organobentonite are added to a mixed solvent of xylene and propylene glycol methyl ether acetate in a mass ratio of 35:20:3. The volume ratio of xylene to propylene glycol methyl ether acetate in the mixed solvent is 4:1. The mixture is heated to 70°C and stirred at 1000 r / min for 3 h to dissolve, thus obtaining the base material.

[0066] Step 4: Preparation of the antifouling paint finished product. By mass, take 30 parts of the prepolymer obtained in Step 1, 15 parts of the microcapsules obtained in Step 2, 25 parts of the base material obtained in Step 3, 10 parts of cuprous oxide, 12 parts of zinc oxide, 15 parts of talc, 3 parts of organobentonite, and 15 parts of xylene. First, mix the prepolymer and the base material and disperse them at 2000 r / min for 30 min. Then add the remaining components and grind them until the fineness is ≤30μm to obtain the antifouling paint for the bottom of the ship.

[0067] In step one, dodecyl mercaptan is used as the chain transfer agent, the heating rate during prepolymerization is 5℃ / min, and the linear velocity at the tip of the stirring paddle is 12m / s.

[0068] In step one, the hydroxyl value of hydroxyethyl methacrylate is 130 mg KOH / g. After the prepolymer synthesis is completed, 0.3% of hydroquinone polymerization inhibitor by mass of the prepolymer is added, stirred evenly, and then cooled to below 40°C before discharge.

[0069] In step two, the flow rate of supercritical CO2 fluid is 10 L / min, and the system pressure fluctuation range is kept ≤ ±0.5 MPa and the temperature fluctuation range is kept ≤ ±1℃ during granulation. The wall thickness of the microcapsules is controlled at 5 μm.

[0070] In step two, the porous silica carrier has a specific surface area of ​​500 m² / g and a pore size of 10 nm. Before microencapsulation, the porous silica carrier is dried in an oven at 120°C for 3 hours and then cooled to room temperature before being mixed with the antifouling active ingredient.

[0071] In step three, the mass ratio of styrene to acrylate in the styrene-acrylate copolymer is 2:1, the acid value of zinc acrylate resin is 80 mg KOH / g, and the cation exchange capacity of organobentonite is ≥100 mmol / 100g.

[0072] In step four, the purity of cuprous oxide is ≥99%, and the particle size distribution D50 is 5μm;

[0073] The purity of zinc oxide is ≥99.5%, and the particle size distribution D50 is 3μm; the whiteness of talc is ≥90%, and the loss on ignition is ≤5%.

[0074] In step four, a three-roll mill is used for grinding, with the front roller rotating at 150 r / min, the middle roller at 250 r / min, and the rear roller at 350 r / min, and the roller gap at 0.1 mm.

[0075] The method also includes step five: antifouling paint curing treatment. The antifouling paint obtained in step four is placed in a sealed desiccator and allowed to cure for 72 hours at a temperature of 27°C and a relative humidity of 55%. During the curing period, the paint is stirred once every 12 hours at a stirring speed of 500 r / min for 10 minutes each time.

[0076] A hydrolytic antifouling paint for ship bottoms made in Wuxi, comprising the following raw materials in parts by weight:

[0077] 30 parts of modified acrylic resin prepolymer, 15 parts of antifouling active component microcapsules, 25 parts of hydrolyzed self-polishing base material, 10 parts of cuprous oxide, 12 parts of zinc oxide, 15 parts of talc, 3 parts of organobentonite, and 15 parts of xylene.

[0078] The structure of the hydrolytic antifouling paint for Wuxi ship bottoms includes a surface hydrolytic release layer and an inner antifouling functional skeleton. The surface hydrolytic release layer is composed of a hydrolytic self-polishing base material, and the inner antifouling functional skeleton is formed by mixing and curing antifouling active component microcapsules, cuprous oxide, zinc oxide and talc.

[0079] Comparative Example 1 differs from Example 1 in that: in step two, the antifouling active components were not microencapsulated in this comparative example, but dihydrocapsaicin, 4,5-dichloro-2-n-octyl-3-isothiazolinone, and porous silica carrier were directly physically mixed.

[0080] Comparative Example 2 differs from Example 1 in that zinc acrylate resin was not added in step three of this comparative example; instead, styrene-acrylate copolymer was used as the hydrolytic self-polishing base material.

[0081] Comparative Example 3 differs from Example 1 in that cuprous oxide was not added in step four of this comparative example, and the antifouling function was achieved solely by organic antifouling agents.

[0082] Comparative Example 4 differs from Example 1 in that: this comparative example does not include the aging process in step five, and is directly packaged and used after preparation and grinding.

[0083] The performance of the hydrolytic antifouling paints prepared in Examples 1-3 and Comparative Examples 1-4 was tested. The test items and methods are as follows:

[0084] Antifouling effectiveness test: Hang the board in the actual sea area and observe the area of ​​marine organisms attached to the board surface every month. The attachment area is less than 5% as effective antifouling, and the effective antifouling duration is recorded.

[0085] Hydrolysis rate test: The paint film thickness loss was measured periodically in artificial seawater at pH 8.1 and temperature 25℃. The hydrolysis weight loss rate per unit time was calculated to characterize the self-polishing performance.

[0086] Adhesion test: The cross-cut test was used to prepare a 150μm dry film on a steel plate. After curing at room temperature for 7 days, 100 grids (1mm×1mm) were cut using a cross-cut tester. After applying the tape, it was quickly peeled off, and the number of grids that fell off was counted.

[0087] Heavy metal leaching rate test: After soaking for 14 days, the amount of copper ions leached out of the soaking solution was measured to assess the environmental friendliness.

[0088] The test data of the antifouling paints prepared in Examples 1-3 and Comparative Examples 1-4 are recorded in the table below:

[0089] Example 1 36 4.2 0 8.5 Example 2 42 5.0 0 9.2 Example 3 48 5.8 0 10.1 Comparative Example 1 18 6.5 1 22.3 Comparative Example 2 24 1.2 2 7.8 Comparative Example 3 12 4.5 0 3.2 Comparative Example 4 30 5.5 3 11.5

[0090] By comparing and analyzing the data in the table, it can be seen that the hydrolytic antifouling paint for Wuxi ship bottoms prepared using the processes in Examples 1-3 has significantly better performance than the hydrolytic antifouling paint for Wuxi ship bottoms prepared in Comparative Examples 1-4. This indicates that the present invention, by using supercritical CO2 fluid to encapsulate and granulate dihydrocapsaicin, 4,5-dichloro-2-n-octyl-3-isothiazolinone, and a porous silica carrier, and by controlling the particle size and wall thickness of the microcapsules, ensures a stable loading of the antifouling active components, while preventing premature loss of active ingredients, achieving long-term release of the antifouling function and reducing the need for recoating the antifouling paint; and by using styrene-acrylate copolymer, acrylic acid... Zinc resin and organobentonite are dissolved in a mixed solvent of xylene and propylene glycol methyl ether acetate. The mass ratio of styrene to acrylate and the acid value of zinc acrylate resin are controlled to ensure the hydrolytic stability of the base material. At the same time, controllable polishing of the paint film surface is achieved, maintaining the self-polishing performance of the antifouling paint and improving the smoothness of the paint film. By sequentially mixing, dispersing and grinding the modified acrylate resin prepolymer, antifouling active component microcapsules, hydrolyzed self-polishing base material and fillers, and then curing the finished product, the density and uniformity of the paint film are ensured. At the same time, the adhesion between the paint film and the substrate is improved, the application adaptability of the antifouling paint is enhanced, and the service life of the antifouling paint is extended.

[0091] By comparing and analyzing the relevant data in the table, it can be seen that the hydrolytic antifouling paint for ship bottoms prepared by the molding process of this invention has excellent long-lasting antifouling properties, controllable hydrolytic self-polishing performance, and good environmental friendliness.

[0092] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0093] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a hydrolytic tin-free antifouling paint, characterized by: Includes the following steps: Step 1: Preparation of modified acrylate resin prepolymer: Methyl methacrylate, butyl acrylate, hydroxyethyl methacrylate and chain transfer agent are mixed in a mass ratio of 35-45:20-30:8-12:0.5-1.5, protected by nitrogen gas, heated to 75℃-85℃, and prepolymerized by stirring at 800-1200 r / min for 1.5-2.5 h to obtain a prepolymer with a solid content of 40%-50%. Step 2: Microencapsulation of antifouling active components. Dihydrocapsaicin, 4,5-dichloro-2-n-octyl-3-isothiazolinone, and porous silica carrier are mixed at a mass ratio of 1-2:0.5-1:5-8. The mixture is then coated and granulated using supercritical CO2 fluid at a pressure of 15-25 MPa and a temperature of 40-50℃ to obtain microcapsules with a particle size of 10-30 μm. Step 3: Synthesis of self-polishing base material by hydrolysis. Styrene-acrylate copolymer, zinc acrylate resin and organobentonite are added to a mixed solvent of xylene and propylene glycol methyl ether acetate in a mass ratio of 25-35:10-20:1-3. The volume ratio of xylene to propylene glycol methyl ether acetate in the mixed solvent is 2-4:

1. The mixture is heated to 60℃-70℃ and stirred at 600-1000 r / min for 2-3 hours to dissolve the material. Step 4: Preparation of the antifouling paint finished product. By mass, take 20-30 parts of the prepolymer obtained in Step 1, 5-15 parts of the microcapsules obtained in Step 2, 15-25 parts of the base material obtained in Step 3, 5-10 parts of cuprous oxide, 8-12 parts of zinc oxide, 10-15 parts of talc, 1-3 parts of organobentonite, and 10-15 parts of xylene. First, mix the prepolymer and the base material and disperse them at 1500-2000 r / min for 20-30 min. Then add the remaining components and grind until the fineness is ≤30μm to obtain the antifouling paint for the ship bottom.

2. The preparation method of a hydrolytically type tin-free antifouling paint for ship bottoms according to claim 1, characterized in that: In step one, the chain transfer agent is mercaptoethanol or dodecyl mercaptan, the heating rate during prepolymerization is 3-5℃ / min, and the linear velocity of the stirring blade tip is 8-12m / s.

3. The preparation method of a hydrolytically type tin-free antifouling paint for ship bottoms according to claim 1, characterized in that: In step one, the hydroxyl value of hydroxyethyl methacrylate is 100-130 mgKOH / g. After the prepolymer synthesis is completed, 0.1-0.3% of hydroquinone polymerization inhibitor is added, and after stirring evenly, the temperature is lowered to below 40°C before discharge.

4. The preparation method of a hydrolytically type tin-free antifouling paint for ship bottoms according to claim 1, characterized in that: In step two, the flow rate of the supercritical CO2 fluid is 5-10 L / min, the pressure fluctuation range of the system is kept ≤ ±0.5 MPa and the temperature fluctuation range is kept ≤ ±1℃ during the granulation process, and the wall thickness of the microcapsules is controlled at 2-5 μm.

5. The preparation method of a hydrolytically type tin-free antifouling paint for ship bottoms according to claim 1, characterized in that: In step two, the porous silica carrier has a specific surface area of ​​300-500 m² / g and a pore size of 5-10 nm. Before microencapsulation, the porous silica carrier is dried in an oven at 120°C for 2-3 hours and then cooled to room temperature before being mixed with the antifouling active ingredient.

6. The preparation method of a hydrolytically type tin-free antifouling paint for ship bottoms according to claim 1, characterized in that: In step three, the mass ratio of styrene to acrylate in the styrene-acrylate copolymer is 1-2:1, the acid value of the zinc acrylate resin is 50-80 mg KOH / g, and the cation exchange capacity of the organobentonite is ≥100 mmol / 100g.

7. The preparation method of a hydrolytically type tin-free antifouling paint for ship bottoms according to claim 1, characterized in that: In step four, the purity of cuprous oxide is ≥99%, and the particle size distribution D50 is 2-5μm; The purity of zinc oxide is ≥99.5%, and the particle size distribution D50 is 1-3μm; the whiteness of talc is ≥90%, and the loss on ignition is ≤5%.

8. The preparation method of a hydrolytically type tin-free antifouling paint for ship bottoms according to claim 1, characterized in that: In step four, a three-roll mill is used for grinding, with the front roller rotating at 100-150 r / min, the middle roller at 200-250 r / min, and the rear roller at 300-350 r / min, and the roller gap at 0.05-0.1 mm.

9. The preparation method of a hydrolytically type tin-free antifouling paint for ship bottoms according to claim 1, characterized in that: The method also includes step five: antifouling paint curing treatment, in which the antifouling paint obtained in step four is placed in a sealed desiccator and allowed to cure for 48-72 hours at a temperature of 25±2℃ and a relative humidity of 50±5%. During the curing period, the paint is stirred once every 12 hours at a stirring speed of 300-500 r / min for 5-10 minutes each time.

10. A hydrolytically soluble tin-free antifouling paint for ship bottoms, prepared by the method described in any one of claims 1-9, characterized in that: The antifouling paint is composed of the following raw materials in parts by weight: 20-30 parts of modified acrylate resin prepolymer, 5-15 parts of antifouling active component microcapsules, 15-25 parts of hydrolyzed self-polishing base material, 5-10 parts of cuprous oxide, 8-12 parts of zinc oxide, 10-15 parts of talc, 1-3 parts of organobentonite, and 10-15 parts of xylene.

Citation Information

Patent Citations

  • Anti-fouling paint containing micro-encapsulation capsaicin and preparation method thereof

    CN101081950A

  • Long-acting self-polishing antifouling paint and preparation method thereof

    CN102732122A